Effective Policing for 21st-Century Israel - Saunders, Jessica (RAND Corporation, 2013)
Israel has changed dramatically in the past two decades. The Israel Police is transforming itself to meet the needs of modern Israel. The Ministry of Public Security, the Ministry of Finance, and the Israel Police asked RAND to conduct a study to address issues of public perceptions and trust in the police, benchmarking the police against other police organizations, performance measurement, and deterrence and crime prevention.